Structural mechanisms of formation of adiabatic shear bands (Fracture and Structural Integrity, 2016)
The paper focuses on the experimental and theoretical study of plastic deformation instability and localization in materials subjected to dynamic loading and high-velocity perforation. We investigate the behavior of samples dynamically loaded during Hopkinson-Kolsky pressure bar tests in a regime close to simple shear conditions. Experiments were carried out using samples of a special shape and appropriate test rigging, which allowed us to realize a plane strain state. Also, the shear-compression specimens proposed in were investigated. The lateral surface of the samples was investigated in a real-time mode with the aid of a high-speed infra-red camera CEDIP Silver 450M. The temperature field distribution obtained at different time made it possible to trace the evolution of plastic strain localization. Use of a transmission electron microscope for studying the surface of samples showed that in the regions of strain localization there are parts taking the shape of bands and honeycomb structure in the deformed layer. The process of target perforation involving plug formation and ejection was investigated using a high-speed infra-red camera. A specially designed ballistic set-up for studying perforation was used to test samples in different impulse loading regimes followed by plastic flow instability and plug ejection. Changes in the velocity of the rear surface at different time of plug ejection were analyzed by Doppler interferometry techniques. The microstructure of tested samples was analyzed using an optical interferometer-profilometer and a scanning electron microscope. The subsequent processing of 3D deformation relief data enabled estimation of the distribution of plastic strain gradients at different time of plug formation and ejection. It has been found that in strain localization areas the subgrains are elongated taking the shape of bands and undergo fragmentation leading to the formation of super-microcrystalline structure, in which the size of grains is ~300nm. Rotational deformation modes give rise to the high angular disorientations of grains. The development of plastic shear instability regions has been simulated numerically. For this purpose, we use a recently developed theory, in which the influence of microshears on the deformation properties of materials has been studied by the methods of statistical physics and thermodynamics of irreversible processes. The results of theoretical and experimental studies suggest that one of the mechanisms of the plastic shear instability and localization of plastic strain at high-velocity perforation is related to structural and kinetic transitions in microshear ensembles.
Keywords: Plastic strain localization; Microdefects; Dynamic loading; Numerical modeling